Pakistan Report on the Observance of Standards and Codes : Accounting and Auditing - World Bank Group (World Bank, Washington, DC, 2017)
Report on the Observance of Standards and Codes Accounting and Auditing (ROSC A&A) assess financial reporting and auditing practices in participating countries. These reports form part of a joint initiative implemented by the World Bank and the International Monetary Fund to review the quality of implementation of internationally recognized standards and principles in 12 key areas (the ROSC program) with a view to promoting financial and economic stability. This report provides an assessment of financial reporting and auditing requirements and practices within the corporate sector in Pakistan and sets forth areas of consideration for improving the institutional environment for accounting and auditing. The ROSC A&A used international benchmarks of good practice governing financial reporting and auditing in the assessment, including International Financial Reporting Standards and International Standards on Auditing. As an update to an earlier assessment that was published in 2005, this report was undertaken following a formal request from the Government of Pakistan.